Pengembangan Aplikasi Pengelolaan Dan Monitoring Perjalanan Dinas (Studi Kasus: SMK Canda Bhirawa Pare) - Nike Wirahayu Cahyaningsih; Denny Sagita Rusdianto; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
There are some documents in official trip, namely official trip orders, official orders and reports on results and finances that are done manually, take a lot of time, writing errors and duplication of incoming data often occurs. In addition, there is the possibility of missing data. Then there is not enough evidence for employees did official travel. Therefore this study will discuss the data collection for each available file and monitoring of each employee. Employees submit official trips and reports during official trips which will then be stored in a database which can then be checked by the administration, treasurer and school principal. The system was developed using PHP 7.2 and JavaScript. The method used is the waterfall because it has a development flow to find out the needs of teachers, principals, administration and treasurers directly and fulfill the needs clearly. Data collection is done by interview. Unit testing, integrating and validating are a test wich will be conducted for functional needs. While compatibility is used for non-functional testing by using sortsite which the result can be accessed by several different web browser.